Sistem Informasi Kepegawaian Pada PT ABC - Sastika, Dwi Apriyanti; Novita, Dien (MDP Student Conference, 2024)
PT ABC is a company operating in the development sector. This company was founded in 2010 and has a total of 27 employees. The current personnel system at PT ABC uses Microsoft Word, Microsoft Excel, WhatsApp, and email as communication media but still predominantly uses paper media for storing personnel documents, and errors and data loss often occur. So, many things could be improved in managing data on attendance, recruitment, leave, promotions, demotions, layoffs, rewards, and punishment. The author used the Rational Unified Process (RUP) method in the system development process by conducting interviews, observations, and literature studies. System design using a system built based on a website using the PHP programming language, Laravel framework, and MySQL database. The personnel information system that will record employee data consists of data on attendance, recruitment, leave, promotion, demotion, layoffs, rewards, and punishment. With the results obtained, there is a personnel information system that can help companies manage employee data effectively and efficiently.